Implementation gas-plasma coatings based on nickel - Hlushkova, D. B.; Bagrov, V. A.; Demchenko, S. V.; Volchuk, V. M.; Kalinin, O. V.; Kalinina, N. E.; Глушкова, Д. Б.; Багров, В. А.; Демченко, С. В.; Волчук, В. М.; Калінін, О. В.; Калініна, Н. Є. (Харківський національний автомобільно-дорожній університет, 2022)
The development of modern technology requires a constant increase in reliability and durability of products.Widely used in the practice of domestic and foreign engineering coatings from electrolytic chromium for several hundred hours are triggered, they are unsatisfactorily working on friction and wear at high temperatures. The subject of the study were powder materials based on nickel PG-SR3 and PG-SR4. The work is devoted to the study of the formation of gasplasma coatings on parts of the cylinder-piston group of internal combustion engines using selffluxing powders based on nickel, as well as the structure and properties change after coating sputtering, its reflow,subsequent hardening. The purpose of this work is to study powder materials applied to the working surfaces of piston rings by gas-thermal spraying. The object of the study are processes of formation of the structure and properties of coatings from powder materials. The presence in the deposited layer of a solid solution based on nickel, carbide phase,borides of chromium and nickel, chromium silicides is established. The greatest macro- and microhardness is possessed by fused layers containing the greatest number of strengthening phases. The conducted researches and industrial tests allowed to introduce the coating into production.
Структура і властивості порошкових газоплазмових покриттів на основі нікелю
Keywords: wear; coating sprayin; structure; macro- and microhardness; зношування; напилення покриття; структура; макро- і мікротвердість; 620.175.2:669.15